CONFORMITY OF TELEVISION PRODUCT IN INDONESIA TO ELECTROMAGNETIC COMPATIBILITY STANDARD FOR RADIATED EMISSION TESTING PARAMETER - Wisnu Ananda (Pusbindiklat - LIPI, 2012)
Indonesia have not had regulations regarding Electromagnetic Compatibility (EMC) yet. But the conformityof electronic products, particularly television, on EMC standards is very important because the emission and immunityfactors of electronics products may affect human health and device performance. The undertaken activitieshere is an EMC testing for Radiated Emission parameter of 10 CRT TV’s and 3 LCD TV’s brands circulating inIndonesia. Test method and limit value used refers to the standard CISPR 13:2009 and done at the Laboratory ofElectronics and EMC Center for Material and Technical Products (B4T) Bandung from March to July 2011. Thepurpose of this activity is to provide an overview about conformity of television products in Indonesia against EMCstandard for Radiated Emission parameter. The results showed that only 3 brands of CRT TV and 1 brand of LCDTV conform to the standard CISPR 13:2009.